(untitled) (قضايا سياسية, 2024)
The research sheds light on the institutional structure of Iraqi federalism, which faces many challenges as it is an experiment that is still incomplete and in continuous development, under relatively unstable political, economic, and societal conditions that are likely to occur with risks. Federal institutions operate under a complex security circumstance, fragile national unity, and an economic situation. Critical, and the absence of a previously federal and democratic culture, and there is no standard that can be used to evaluate the work of federal institutions, because every federal experience is a unique experience in itself. Not to mention the unbalanced relationship between the federal government and the regional governments, which was established by the Iraqi Constitution of 2005. What strained the political process and threatened the stability of Iraq was the process of distributing power among the various Iraqi components and the approach to political containment, which led to the complexity of the federal decision-making process and challenged the status of government institutions. On the other side, there is the Kurdistan region, with its broad decentralized political powers. which has asymmetric relations with the federal government, and works to strengthen its independence. It applies the articles of the 2005 Constitution and violates it at the same time in order to assert its interests and control the affairs of the region, and to prevent the federal government from having any effective role in Issues of the borders of the Kurdistan Region and Kirkuk and the control and management of oil resources. Despite the presence of all these problems, we see the role of the Federal Supreme Court as effective in settling disputes and resolving conflicts between the federal government and the regional government through a set of binding decisions that corrected the course of political action and contributed to resolving the outstanding problems, especially those Related to oil resources management.